Comparison and selection of coagulants between moringa oleifera and aluminium sulfate (ALUM) - Lim Bee Sian (School of Environmental Engineering University Malaysia Perlis, 2011)
This study was designed to investigate the efficiency of using two coagulants that is natural coagulant and chemical coagulant in Methylene Blue colour removal. In the study of the Natural Goagulant that is M.O the most effective of the coagulant are 5 % M.O. in 100 ml NaCI that is achieve 56% removal rate in 100 mg/L Methylene Blue. The study show that the colour removal of M.O in different extraction method. For extraction with distilled water, the highest removal efficiency is 10 % in dosage 80 ml of M.O. . For extraction of M.O with NaCI the highest efficiency is 70% in dosage 80n ml. From the result we can see that the extractions of M.O. with NaCI are 7 times higher that extraction of M.O with distilled water.